Wholesome bowls : food for mind, body & soul - Delport, Melissa (Food photographer) (Nourish, 2023)
Provides over ninety recipes for bowl meals designed for mindful eating, including such recipes as Turkish eggs with spicy sesame drizzle, chicken fajita bowls, vegan sweet potato and chili brownies, and roasted celeriac and mushroom soup.